JEP 2021
DOI: 10.7176/jep/12-6-13
|View full text |Cite
|
Sign up to set email alerts
|

Managing Learner Behaviour in a Virtual Classroom: Experiences of Selected Private High School Teachers in Bulawayo Metropolitan Province, Zimbabwe

Abstract: The study examined experiences of private high school teachers in managing learners' behaviour in virtual classrooms. The study was motivated by paradigm shift from physical classroom to virtual classroom in most educational institutions globally because of corona virus pandemic. A qualitative study, rooted in interpretive paradigm employed case study design. The participants who constituted ten teachers were purposively selected from two private high schools in Bulawayo Metropolitan Province. The data solicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…For instance, a study conducted by Omodan et al (2018) revealed that Nigerian secondary schools are inadequately equipped with the necessary human and material resources required for effective classroom management, ultimately impacting learner achievement adversely. Additionally, Sibanda (2021) highlighted that the Ministry of Primary and Secondary Education (MOPSE) in Zimbabwe semphasises the importance of nurturing an environment that promotes self-discipline among students, supplemented by proactive and positive disciplinary interventions. According to a study conducted in Indonesia, Affandi et al (2000) highlighted the challenges related to classroom management can be classified into challenges that come from the teacher and students.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a study conducted by Omodan et al (2018) revealed that Nigerian secondary schools are inadequately equipped with the necessary human and material resources required for effective classroom management, ultimately impacting learner achievement adversely. Additionally, Sibanda (2021) highlighted that the Ministry of Primary and Secondary Education (MOPSE) in Zimbabwe semphasises the importance of nurturing an environment that promotes self-discipline among students, supplemented by proactive and positive disciplinary interventions. According to a study conducted in Indonesia, Affandi et al (2000) highlighted the challenges related to classroom management can be classified into challenges that come from the teacher and students.…”
Section: Introductionmentioning
confidence: 99%